The Museum of Sexual Diversity as a complex information ecology: a study of its findability and pervasive information architecture - Brito, Jean Fernandes [UNESP]; Martinez-ávila, Daniel; Vechiato, Fernando Luiz; Vidotti, Silvana Aparecida Borsetti Gregorio (Biblioteca Central da UNB, 2020)
Considering the importance of understanding the Museum of Sexual Diversity of the city of São Paulo as a complex information ecology, and provided that it is composed of its analog and digital information environments, this paper aims to evaluate the museum based on the attributes of findability and pervasive information architecture using a checklist and a participatory observation. In general, the Museum of Sexual Diversity presents, in its great majority, a partiality regarding the attributes of findability of information. Because it is a complex information ecology, it presents a diversity of factors involved. We noticed that the major problems that we found relate to the topics of information discovery and the mediation of information subjects; and the lack of elements of accessibility on the website which would make it possible to expand the access to information for people with disabilities. Through this study it was possible to enhance the dissemination of ideas related to the information subjects in the process of production and organization of information, making the digital informational environment more collaborative and interactive.
El Museo de la Diversidad Sexual como ecología informacional compleja: un estudio sobre la óptica de la encontrabilidad de la información y la arquitectura de la información pervasiva
O Museu da Diversidade Sexual como ecologia informacional complexa: um estudo sob a ótica da encontrabilidade da informação e arquitetura da informação pervasiva
Keywords: Complex information ecologies; Findability of information; Museum of Sexual Diversity; Pervasive architecture of information